A Taxonomy of the Functions Supported by Browsing Facilitators - Préfontaine, Gabrielle; Bartlett, Joan C.; Toms, Elaine G. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
Browsing is a key method by which humans obtain information, yet it is often neglected in the design of search interfaces. In this paper, we selectively examine the literature on tools developed to facilitate browsing and propose the root of a taxonomic tree of the processes that browsing facilitators need to support. Finally, we explore how a select set of browsing tools currently support these functions.